The influence of the experiments in teaching natural sciences on the quality of knowledge of the 4th form pupils - Bernotas , V. (Psichologija, 1973)
On the ground of experimental material the article deals with a short characteristic of the experiments in teaching natural sciences in the 4th form. The author also shows the essence of the experiments, their principal similarities and differences from the experiments carried out by scientists. By means of concrete examples the author shows that the teaching experiments, depending on the didactic objectives, may be used in different parts of the process of teaching: explaining a new material, fixing or checking pupils’ knowledge. The author reveals the possibilities of the usage of experiments in different lessons of natural sciences, gives the description of pupils’ preparation for independent experiments and observations and determines their efficiency in the process of teaching. The article shows that the experiments help to develop pupils’ logical thinking, their independence, form elementary skills of research work.
Keywords: teaching of natural sciences; experiments; quality of knowledge